Evolution of Electrogenic Ammonium Transporters (AMTs) - McDonald, Tami R.; Ward, John M. (Frontiers in Plant Science, 2016)
The ammonium transporter gene family consists of three main clades, AMT, MEP, and Rh. The evolutionary history of the AMT/MEP/Rh gene family is characterized by multiple horizontal gene transfer events, gene family expansion and contraction, and gene loss; thus the gene tree for this family of transporters is unlike the organismal tree. The genomes of angiosperms contain genes for both electrogenic and electroneutral ammonium transporters, but it is not clear how far back in the land plant lineage electrogenic ammonium transporters occur. Here, we place Marchantia polymorpha ammonium transporters in the AMT/MEP/Rh phylogeny and we show that AMTs from the liverwort Marchantia polymorpha are electrogenic. This information suggests that electrogenic ammonium transport evolved at least as early as the divergence of bryophytes in the land plant lineage.